Political National law to of Islamic law - H.M. Yunus; Anwar Sulaiman; Hj. Asmak Ul Hosnah; Yenny Febrianty (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
Political law is two interrelated meanings that cannot be separated, because politics is a strategy to achieve power by any means. While the law is a means or tool used when power cannot achieve the purpose of power. Where the law is essentially to protect individuals or communities from the arbitrary actions of power holders and / or parties who commit acts of justice, in the end to get a sense of justice in the nation and state, in the thought that the state in the development of human civilization is closely related to religion, the relationship between the two occurs the transformation of Islamic law in the development of Indonesian legal politics, both of which experience ups and downs with the development of human thought about the function of the state in his personal life and at the same time in the relationship between religion and the state he embraces. This research aims to describe Political Law in Islamic Law. This research uses a qualitative approach with the method of literature (Library research). The reform era research data outlines the configuration of a democracy-based legal political system. The system emphasizes the need to organize laws that are populist and responsive, not repressive and authoritarian. Legal regulation policies must reflect the aspirations of the citizens of the community/state. The legal products achieved must be a mecca in solving legal problems and achieving the goals of the life of the nation and state. The substance of the law is built not to serve the interests of the ruling elite, but must be an instrument and guideline in organizing legal development aimed at realizing physical and mental welfare.